Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 16, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 16, 1930. The intra party war was lively Connecticut. Hawley disapproved of Johnson's course as president as he long had of Dixon's as senator. The Press printed a letter from Washington in February, possibly written by Hawley, exposing what it called Dixon's attempt to destroy the republican party, referring to the "prominent senator" conversation with President Johnson. The Courant vigorously denied the accusations against the senator. The union republican convention was set for February 14. There were two tickets in the field for delegates. Those chosen from Hartford were Henry K. W. Welch, father of Archibald A. Welch and partner of Nathaniel Shipman, the father of Arthur L. Shipman and Hawley's great friend; E. N. Kellogg, David Clark and Gorge P. Bissell. All these were strong Hawley men, although unpledged.
1 electronic record. Scanned newspaper article. 2 image scans. 1.31 MB (1,374,775 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 36.9 MB (38,733,961 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers